Urban Seismomorphoses Seismic Vulnerabilities, an Embarrassing Legacy - Stephane Cartier; Cloe Valette; Hafida Mediene (Journal of Risk Analysis and Crisis Response (JRACR), 2012)
Seismic vulnerability challenges sustainable urbanism. Antioch, Manosque and Oran, three Mediterranean cities destroyed by earthquakes, demonstrate how preservation of urban patrimony protects populations. The methodological pattern “urban seismic patrimonial strategies” cross investment and patrimonial care demonstrate natural hazards mitigation as a factor of urban policy. Urban patrimonial managers are unaware of seismic threat which obliges them to explain liabilities. Buildings evolution observation indicates urban phases. According urban policy reshape urban morphology and amplify social vulnerability.